Comparative Study of Implementation of Online Learning at the Tarbiyah and Teacher Training Faculty and the Faculty of Adab and Humanities - khotima, Husnul; Aisyah, Neng; Marsudin, Ahmad Rizaldi; Oviyanti, Fitri; Maryamah, Maryamah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research examines the comparison of the implementation of online learning at the Tarbiyah and Teacher Training Faculty and the Faculty of Adab and Humanities at UIN Raden Fatah Palembang using a qualitative approach with comparative studies, which aims to comprehensively investigate the differences in blended learning strategies and policies in the two educational institutions. Through data collection methods that include direct observation, in-depth interviews with academic stakeholders, and analysis of official documents, this research explores significant variations in the implementation of hybrid learning models, with a primary focus on the proportion of online learning, technology platforms used, and the pedagogical impact of different approach. Key findings show that the Tarbiyah and Teacher Training Faculty implements a model with 40% online learning and 60% offline, utilizing e-learning for administrative management, while the Adab and Humanities Faculty limits online learning to 30% using the Zoom and Google Meet platforms. These differences reflect institutional flexibility in responding to digital educational challenges, while also revealing the complexity of pedagogical adaptations required in the modern higher education context. This research not only identifies technical variations in the implementation of blended learning, but also analyzes the strategic implications of different approaches, including the potential impact on the quality of academic interactions, the effectiveness of knowledge transfer, and the need for continuous professional development for teaching staff. The research conclusion emphasizes the importance of systematic evaluation and continuous adjustment in the hybrid learning model, while underscoring the blindness of a more standardized approach that still pays attention to the unique characteristics of each faculty in implementing blended learning strategies.